Vertical Distribution of the Monthly Mean Values of the Air Temperature above the Territory of Kakheti (Georgia) in the Central Months of the Year 2012-2016 - Jamrishvili, Nino K.; Tavidashvili, Khatia Z. (Journals of Georgian Geophysical Society, 2017)
The data about the changeability of the mean five-year values of the daily values of the air temperature above Kakheti for the central months of year for the period from 2012 through 2016 are cited. The statistical characteristics of the air temperature at the different levels in the range of heights from 0.54 to 27 km are represented. In particular, are cited: the data about the vertical distribution of the average monthly values of the air temperature during January, April, July and October; the mean value of the gradient of air temperature for the indicated months in the layer of the atmosphere from 0.54 to 8.5 km; the average monthly values of height of zero isotherm. It is noted, that heights of zero isotherm for July and October into 2012-2016 respectively by 0.215 and 0.506 km are higher than the same values in 1958-1961.